1991
DOI: 10.1071/rd9910601
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen concentration and protein source affect the development of preimplantation goat embryos in vitro

Abstract: The effect of oxygen concentration and the source of protein in culture medium on the development of 2- to 4-cell goat embryos in vitro was investigated. Embryos were collected from superovulated Angora-Cashmere-cross goats 48 h after ovulation and cultured for 6 days in synthetic oviduct fluid (SOF) medium under one of two oxygen concentrations (20% or 7%) and in the presence of one of five protein sources; Miles bovine serum albumin (Miles BSA), Commonwealth Serum Laboratory bovine serum albumin (CSL BSA), g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(61 citation statements)
references
References 24 publications
4
54
0
3
Order By: Relevance
“…Oxygen at a concentration of 20% (atmospheric) has been shown to adversely affect embryonic development compared with embryos cultured at 5% (Quinn & Harlow 1978, Batt et al 1991, Gardner & Lane 1996. These data further support the notion that it is not appropriate to culture the preimplantation mammalian embryo in the presence of atmospheric oxygen.…”
Section: Discussionsupporting
confidence: 75%
“…Oxygen at a concentration of 20% (atmospheric) has been shown to adversely affect embryonic development compared with embryos cultured at 5% (Quinn & Harlow 1978, Batt et al 1991, Gardner & Lane 1996. These data further support the notion that it is not appropriate to culture the preimplantation mammalian embryo in the presence of atmospheric oxygen.…”
Section: Discussionsupporting
confidence: 75%
“…Toxic effects of atmospheric oxygen concentration under an ordinary culture conditions and beneficial effect of lower O 2 concentrations (5-7%) on embryo development have been reported in mouse [1,[30][31][32][33][34], hamster [2,35], rat [3], pig [4,[36][37][38], sheep [5,39,40], goat [6], cow [5,[41][42][43][44] (Fig. 2) and human [7,[45][46][47].…”
Section: Effects Of Oxidative Stress On Development Of Preimplantatiomentioning
confidence: 99%
“…20%) [1][2][3][4][5][6][7]. Detrimental effect of O 2 concentration has correlated with the generation of ROS [8,9].…”
mentioning
confidence: 99%
“…In contrast, human serum contains a heterogeneous mixture of many proteins and other factors. It has been demonstrated that human serum enhances blastocyst formation in cow [19], goat [1], sheep [9] and pig [30] embryos in culture, while on the other hand it inhibits embryo development in mice [21]. In feline embryos, it appears that unidentified factors in human serum stimulate blastocoel cavity formation without effect on cell division.…”
Section: Discussionmentioning
confidence: 99%